Mangrove cultural services and values: Current status and knowledge gaps. Issue 5 (19th July 2022) - Moore, Alex C.; Hierro, Luis; Mir, Neena; Stewart, Taylor
Abstract: The evaluation of cultural services and values in coastal and marine environments has been steadily increasing over the last decade, though significant knowledge gaps remain regarding specific ecosystems such as mangrove forests. To identify these gaps, we provide a summary of the current literature on mangrove cultural services and values, indicate priority areas where additional research is needed and highlight some of the potential sociocultural impacts associated with mangrove losses. The studies included in this synthesis identified or evaluated 16 cultural services and values linked to mangrove habitats across 25 countries, representing roughly 22% of global mangrove regions. We observed differences in assessment frameworks, methods, and author affiliations that may have influenced research outcomes with implications for future study design. Toward this end, we provide specific recommendations to improve future mangrove CSV studies. Cultural services are often the most valued services ecosystems provided to stakeholders and local communities. As such, it is our hope that identifying these gaps will provide an impetus for the study of mangrove cultural services and values, thereby resulting in an improved understanding of the interactions between people and mangroves for the benefit of both. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.